The intestinal interferon system and specialized enterocytes as putative drivers of HIV latency - Creighton, Rachel L.; Hughes, Sean M.; Hladik, Florian; Gornalusse, Germán G. (Frontiers in Immunology, 2025)
The barrier to HIV cure is the HIV reservoir, which is composed of latently infected CD4+ T cells and myeloid cells that carry stably integrated and replication-competent provirus. The gastrointestinal tract (GIT) contains a substantial part of the HIV reservoir and its immunophysiology could be especially conducive for HIV persistence and reactivation. However, the exact cellular microenvironment and molecular mechanisms that govern the renewal of provirus-harboring cells and proviral reactivation in the GIT remain unclear. In this review, we outline the evidence supporting an overarching hypothesis that interferon activity driven by specialized enterocytes creates a microenvironment that fosters proliferation of latently infected CD4+ T cells and sporadic HIV reactivation from these cells. First, we describe unique immunologic features of the gastrointestinal associated lymphoid tissue (GALT), specifically highlighting IFN activity in specialized enterocytes and potential interactions between these cells and neighboring HIV susceptible cells. Then, we will describe dysregulation of IFN signaling in HIV infection and how IFN dysregulation in the GALT may contribute to the persistence and reactivation of the latent HIV reservoir. Finally, we will speculate on the clinical implications of this hypothesis for HIV cure strategies and outline the next steps.